ID 61 – Electrophysiological correlates of experimental pain perception. Issue 3 (March 2016) - Chouchou, F.; Perchet, C.; Garcia-Larrea, L.
Abstract : Objective: Identify pain markers remains a major scientific and medical problem. In this view, we studied the dynamics of central and autonomic responses to tonic painful stimuli. Methods: Twelve healthy subjects underwent 2 tonic painful (hand electrical stimulations and 10°C water immersion) and 2 non-painful (hand 15 °C water immersion and stressful cognitive) tests during 2 min. Continuous 128 electroencephalographic (EEG) derivations, pupillary, electrodermal conductance, heart rate and blood pressure were recorded, with pain ratings. Time–frequency analyses were applied to EEG and autonomic measures. Loreta® and BESA were used to estimate the location of EEG activities. Results: A significant contralateral decrease in alpha power occurred in parietal-central regions during the 2 painful but not in non-painful conditions, with involvement of somatosensory, dorsolateral and anteromedial prefrontal cortices. Electrodermal conductance and pupil dilation showed large and reproducible variations during painful and stressful non-painful conditions, while cardiovascular responses were only responsive to the latter. Conclusions: These results suggest a specific electrophysiological response to experimental pain, based on the combination of EEG-alpha power decrease with electrodermal and pupil autonomic responses. Key message: This work highlighted a combination of non-invasive pain markers that may be tested in various clinical settings to detect pain in non-communicative patients.